High strain rate and elevated temperature compressive properties of magnesium alloy AZ31B - Myat, Thu. (2012)
Magnesium alloys are highly studied due to their low density in comparison to aluminum alloys and steel alloys. In this project AZ31B magnesium alloy is used to study deformation behavior of metal. Cylindrical specimens with same dimension but different fabricated directions (Transverse, Angular, Rolling and Normal) are used in compressive split Hopkinson bar test. Experiments are carried out under different temperature and strain rate. Two set of strain rates used in this project are 1000s-1 and (1700s-1-2000s-1). Each strain rate involves two different temperatures tests, which are at -30˚C and 250˚C. Minimum of 3 or 4 specimens are used for each condition to get high repeatability. In this report the behaviors of material are analyzed and as well as some important parameter such as m (strain rate sensitivity coefficient), n (strain hardening exponent), u (energy) are also discussed.